2011
DOI: 10.1007/s12010-011-9479-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Perspective for Effective Bioremediation

Abstract: Identification of factors which can influence the natural attenuation process with available microbial genetic capacities can support the bioremediation which has been viewed as the safest procedure to combat with anthropogenic compounds in ecosystems. With the advent of molecular techniques, assimilatory capacity of an ecosystem can be defined with changing community dynamics, and if required, the essential genetic potential can be met through bioaugmentation. At the same time, intensification of microbial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 113 publications
0
30
0
Order By: Relevance
“…This again supports the idea that the bacterial communities in the EIFs have adapted to and are thriving due to the higher nutrient and carbon loads found in the pulp and paper effluent. This is a positive result as diversity has been linked to soil health and robustness [3], and also it seems that bacterial communities present in EIFs managing the paper mill effluent pollutants as additional carbon source [27]. It seems that the pulp and paper mill effluent has not adversely affected the soil community and in fact the structural diversity has increased.…”
Section: Phylogenetic Analysis Of 16s Rrna Gene Clone Librarymentioning
confidence: 97%
“…This again supports the idea that the bacterial communities in the EIFs have adapted to and are thriving due to the higher nutrient and carbon loads found in the pulp and paper effluent. This is a positive result as diversity has been linked to soil health and robustness [3], and also it seems that bacterial communities present in EIFs managing the paper mill effluent pollutants as additional carbon source [27]. It seems that the pulp and paper mill effluent has not adversely affected the soil community and in fact the structural diversity has increased.…”
Section: Phylogenetic Analysis Of 16s Rrna Gene Clone Librarymentioning
confidence: 97%
“…Acclimatization, is an additional step, has been included to treat wastewater sludge in treatment plant. Introduction of genetically modified microorganisms (Paliwal et al 2012) and metal-resistant marine bacteria (Poirier et al 2013) can also be used as advance bioremediation techniques.…”
Section: Strategies For Bioremediationmentioning
confidence: 99%
“…Under slurry phase bioremediation, a more rapid process, contaminated soil combines with water and other additives in a large tank called a bioreactor and mixed to keep the microorganisms in contact with the contaminants in the soil to create the optimum environment for the microorganisms to degrade the contaminants. By ensuring proper sampling techniques and maintaining controlled conditions with collected core sample, the effective ex situ bioremediation can be achieved (Paliwal et al 2012). A pilot study of 6 months of biopile farming confirmed that bioaugmentation and biostimulation could enhance the bioremediation of petroleum-contaminated soil (Cheng et al 2009).…”
Section: Ex Situ Bioremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl ester derivatives from the extracted lipids are used to evaluate microbial community structure, but they may be used only in pure cultures of bacteria. Monitoring of community structure is possible by using biosensors which are specific bioactive compound emitting signals [87,88].…”
Section: Methods Of Effectiveness Evaluation Of the Bioremediation Prmentioning
confidence: 99%